Optimalisasi Kadar Asam Asetat Ananas Comosus l dengan Penambahan Induk Cuka - Fitria Fitria; Mimin Septiani; Irhamni Nuhardin (Jurnal Teknik Juara Aktif Global Optimis, 2021)
Ananas comosus L. (Pineapple) is one of the superior fruit commodities in Indonesia. The amount of production in 2016 pineapples placed fourth after bananas, oranges and mangoes which amounted to 1.4 million tons/year. Pineapple production for East Kalimantan, Balikpapan city has an area of 8,572 hectares of pineapple with a production of 7,206 tons of pineapple. Pineapple skin contains 17.53% carbohydrates and 13.65% sugar. This led researchers to develop the manufacture of acetic acid from the skin waste of Ananas comosus L. The research method consists of materials used namely, pineapple skin, water, granulated sugar, yeast, vinegar, ammonium sulfate, oxalic acid, sodium hydroxide, pp indicators and aquades obtained from STTI Bontang laboratory. The working procedure of this study consists of 3 stages of the method: the first fermentation stage with the addition of Saccharomyces cerevisiae, the second fermentation stage with variations in the addition of the parent vinegar and the calculation of acetic acid levels with time intervals of 2 days /sample (days 16, 18, 20, 22 and 24). The third stage is carried out by alkaline method. Optimum results from research with the main variation of vinegar and fermentation time were obtained on the 20th day with the addition of a 2.3 mL vinegar master obtained a acetic acid content of 6.24 g/mL. Further researchers are expected to develop better analytical methods to make the concentration of acetic acid obtained more optimal.